Reduced Root Cortical Cell File Number Improves Drought Tolerance in Maize - Chimungu, Joseph G.; Brown, Kathleen M.; Lynch, Jonathan P. (Plant physiology (Bethesda), 2014)
We tested the hypothesis that reduced root cortical cell file number (CCFN) would improve drought tolerance in maize (Zea mays) by reducing the metabolic costs of soil exploration. Maize genotypes with contrasting CCFN were grown under wellwatered and water-stressed conditions in greenhouse mesocosms and in the field in the United States and Malawi. CCFN ranged from six to 19 among maize genotypes. In mesocosms, reduced CCFN was correlated with 57% reduction of root respiration per unit of root length. Under water stress in the mesocosms, genotypes with reduced CCFN had between 15% and 60% deeper rooting, 78% greater stomatal conductance, 36% greater leaf CO₂ assimilation, and between 52% to 139% greater shoot biomass than genotypes with many cell files. Under water stress in the field, genotypes with reduced CCFN had between 33% and 40% deeper rooting, 28% lighter stem water oxygen isotope enrichment (δ¹⁸O) signature signifying deeper water capture, between 10% and 35% greater leaf relative water content, between 35% and 70% greater shoot biomass at flowering, and between 33% and 114% greater yield than genotypes with many cell files. These results support the hypothesis that reduced CCFN improves drought tolerance by reducing the metabolic costs of soil exploration, enabling deeper soil exploration, greater water acquisition, and improved growth and yield under water stress. The large genetic variation for CCFN in maize germplasm suggests that CCFN merits attention as a breeding target to improve the drought tolerance of maize and possibly other cereal crops.